2011
DOI: 10.1093/mp/ssr055
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Signal off the STARTing Block

Abstract: The year 2009 marked a real turnaround in our understanding of the mode of abscisic acid (ABA) action. Nearly 25 years had elapsed since the first biochemical detection of ABA-binding proteins in the plasmalemma of Vicia guard cells was reported. This recent--and laudable--achievement is owed largely to the discovery of the soluble ABA receptors whose major interacting proteins happen to be some of the most well-established components of earliest steps in ABA signaling. These soluble receptors, with the double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 162 publications
(261 reference statements)
1
71
0
Order By: Relevance
“…The impairment of the ABAinduced ROS production in the ost1 mutant could be bypassed by externally applied H 2 O 2 . Recently, it was shown that NADPH oxidases could be SnRK2s' cellular substrates (for review, see Hubbard et al, 2010;Umezawa et al, 2010;Joshi-Saha et al, 2011). A recombinant cytosolic part of one of the Arabidopsis NADPH oxidases, AtrbohF, produced in a bacterial system is phosphorylated by SnRK2.6/OST1 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The impairment of the ABAinduced ROS production in the ost1 mutant could be bypassed by externally applied H 2 O 2 . Recently, it was shown that NADPH oxidases could be SnRK2s' cellular substrates (for review, see Hubbard et al, 2010;Umezawa et al, 2010;Joshi-Saha et al, 2011). A recombinant cytosolic part of one of the Arabidopsis NADPH oxidases, AtrbohF, produced in a bacterial system is phosphorylated by SnRK2.6/OST1 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that OST1, a protein kinase that regulates SLAC1 activity in the ABA pathway, may be a central integrator of CO 2 and ABA signal transduction in the regulation of SLAC1 in guard cells. While the ABA signal connects to OST1 through ABA receptors and 2C-type protein phosphatases 5,49 , it is not known how the CO 2 signal is linked to OST1. We thus tested the possibility that OST1 may serve as a downstream target of HT1.…”
Section: Rhc1 Is Required For Activation Of the S-type Channelsmentioning
confidence: 99%
“…Water deficit draws down water potential in all plant tissues and may directly impair turgor pressure in the guard cells surrounding the stomatal pores, thus reducing stomatal aperture (Buckley, 2005;Peak and Mott, 2011). In parallel, accumulation of ABA, whether synthesized in roots Borel et al, 2001) or leaves (Christmann et al, 2005(Christmann et al, , 2007Ikegami et al, 2009;McAdam et al, 2016), directly impacts on guard cells to close stomata (Kim et al, 2010;Joshi-Saha et al, 2011).…”
mentioning
confidence: 99%